COP26: What Does It Mean for the Agriculture Sector?. (1st February 2022) - Blake, Robin
Climate change challenges and the urgent need to take things seriously were once again thrust into the spotlight in October and November 2021 with the 26th United Nations Climate Change Conference (COP26) held in Glasgow under the presidency of the United Kingdom, in partnership with Italy. COP stands for Conference of the Parties, and the summit was attended by the countries that signed the United Nations Framework Convention on Climate Change (UNFCCC) ? a treaty agreed in 1994. Billed by many as the most significant climate event since the 2015 Paris Agreement, COP26 aimed to accelerate action towards the goals of both the UNFCCC treaty and Paris Agreement, such as for every country to work together to limit global warming to 1.5°C. Nationally Determined Contributions (NDCs) were central to the Paris Agreement and outlined efforts from each country to reduce national emissions and adapt to the impacts of climate change. Unfortunately, the commitments laid out in Paris in 2015 did not come close to achieving the 1.5°C target, and with the window for action becoming ever smaller, there was substantial pressure on Glasgow to deliver something meaningful. Following two weeks of intense negotiations, COP26 finally ended with nearly 200 countries agreeing the Glasgow Climate Pact. Crucially this pact keeps the 1.5°C reduction alive and completes the Paris Rulebook, a set of guidelines for how the Paris Agreement will be delivered including a transparency process to hold countries accountable as they deliver on their targets. But what about agriculture? Despite being the second largest driver of climate change behind the energy sector, and therefore central to meeting emissions reductions and achieving the 1.5°C target, the general consensus was that the agriculture sector did not feature prominently enough at COP26, and that reliance on major pledges and pacts disguised a lack of detail on exactly how action would be achieved. Under the UNFCCC there is only one program focussed on agriculture ? the Koronivia Joint Work on Agriculture (KJWA) which was established at COP23 in 2017 and aims to address agricultural issues through the lens of climate change. It is composed of six interrelated topics, namely soils, nutrient use, water, livestock, methods for assessing adaptation, and the socioeconomic and food security dimensions of climate change across the agricultural sectors. The process was scheduled to finish at COP26; however, by the end of the meeting there were still many areas of disagreement and so these will need to be ironed out in the future. Furthermore, despite pledging action, none of the updated NDCs submitted by the G20 nations prior to COP26 included specific targets on how commitments made for their agricultural sectors would actually be achieved in practice. Many of the current challenges in agriculture are political in nature, whether it is the desire of developed countries to reduce meat and dairy consumption and move towards more plant-based diets, or the reluctance of developing countries to agree, or discussions on farm subsidies, so it is perhaps not surprising that these challenges were not tackled. Agriculture plays a key role on both sides of the climate change debate as both a source and sink for emissions. Approximately 20% of global anthropogenic greenhouse gas (GHG) emissions including carbon dioxide, methane and nitrous oxide come from agriculture, forestry and land use. This value increases to 31% when considered across the whole agrifood system that includes crops and livestock. When split individually, agrifood systems globally account for 21% of carbon dioxide emissions, 53% of methane emissions and 78% of nitrous oxide emissions. Whilst the principal GHG emitted by most sectors is carbon dioxide, the agricultural sector is unusual in that direct emissions of methane and nitrous oxide, in particular, are far higher. Given the importance of these GHGs both as key drivers of climate change, and to the agricultural sector, it is timely to review COP26 discussions in this area.